(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
In the present work, the enthalpies of mixing of liquid alloys of the ternary Mn-Al-Gd system have been calculated using the regular solution model by the Redlich-Kister-Muggianu formula. Also a comparison was made of calculated values of enthalpies of mixing in this system with the experimentally determined thermochemical properties of liquid alloys of the Mn-In-Gd ternary system obtained previously. In general, we estimate that the values of the enthalpies of mixing in the Mn-Al-Gd ternary system should be more exothermic than in the Mn–In-Gd one. This fact can be explained taking into consideration the main features of the component interaction in the boundary binary systems, namely, such important characteristics as electronegativity of the components, their electron work functions and alarge difference in size of atoms. It can be concluded that it is the binary Mn–Al system that makes a significant contribution to the formation energy of ternary alloys. An imaginary line drawn through the points of maximum curvature of the isoenthalpic lines is considerably shifted towards the binary Mn–Al boundary, thus expanding significantly the region of rather exothermic enthalpies of mixing in the corresponding ternary system. For the two indicated ternary systems the size mismatch entropy has been calculated within the framework of hard spheres model and the Sσ/kB parameter has been determined. On the basis of the comprehensive analysis carried out, the criteria for the probability of occurrence of regions of easy amorphization in these ternary systems are proposed. The determination of the topology of the mixing enthalpy surface and the Sσ/kB parameter for the melts of studied ternary systems together with the data on binary and ternary compounds existing in these systems allowed to reasonably assume the concentration regions where the investigated ternary alloys have tendency for easy amorphization while rapid cooling of the melt. The simultaneous realization of the following three conditions was taken as a criterion for the possible existence of a region of easy amorphization: the absolute value of the enthalpies of mixing is at least 6 kJ / mol, the Sσ/kB parameter is not less than 0.3–0.4 and a certain distance from the concentration region corresponding to the exact composition of binary or ternary compounds.